Dendrimer end-terminal motif-dependent evasion of human complement and complement activation through IgM hitchhiking - Lin-Ping Wu (Nature Portfolio, 2021)
Understanding nanomaterials interactions with complement is important for a number of applications. Here, the authors study the interaction of sub 6 nm dendrimers with complement and show the small dendrimers escape complement activation but do interact with IgM to trigger lectin-pathway complement activation.